SAT0059 APOLIPOPROTEIN B DERIVED PEPTIDES INHIBIT PRODUCTION OF PRO-INFLAMMATORY CYTOKINES IN PBMC OF RHEUMATOID ARTHRITIS (RA) PATIENTS AND IMPROVE ARTHRITIS IN ANIMAL MODEL OF RA. (June 2019) - Park, Ji Soo; Lee, Joo Youn; Yoo, Hyun Jung; Kim, Jeong Yeon; Lee, Ji Hye; Kim, Seon Uk; Kim, Ra Ham; Park, Jin Kyun; Lee, Eun Young; Lee, Eun Bong; Yi, Eugene C.; Song, Yeong Wook
Abstract : Background: Alpha-enolase (ENO1) is a multifunctional glycolytic enzyme. The cell-surface expression of ENO1 is increased in monocytes isolated from peripheral blood mononuclear cells (PBMCs) of RA patients. In previous experiments, we reported apolipoprotein B (apoB) to be as a novel ligand of cell surface expressed ENO1 and to enhance chronic inflammation in RA (1). Objectives: This study was performed to evaluate agonistic or antagonistic function of peptide sequences within apoB, which modulated severity of arthritis in K/BxN serum transfer arthritis mouse model. Methods: Peptides binding to ENO1 were evaluated by peptide microarray. Peptides were designed to have twelve amino acids lengths with ten amino acids overlap. Levels of pro-inflammatory cytokines produced by PBMCs were measured after treatment with peptides in RA patients and healthy controls (HCs). To evaluate the antagonistic function of peptides, RA PBMCs pre-treated with peptides were stimulated with apoB and pro-inflammatory cytokines were measured in culture supernatant. Peptides were injected in K/BxN serum transfer mice and we measured the thickness of ankles and arthritis score to determine whether peptides could reduce arthritis severity. Results: Among eighty five peptides from apoB, five peptides exhibited strong binding to ENO1. Two peptides increased production of pro-inflammatory cytokines, IL-1β, IL-6 and TNF-α, but three peptides did not change levels of pro-inflammatory cytokines in RA and HC PBMCs. However the three peptides reduced production of pro-inflammatory cytokines in RA PBMCs stimulated with apoB. These three peptides were named IP (inhibitory peptide)1, IP2 and IP3. IPs were injected after induction of the arthritis in K/BxN serum transfer mice in vivo. Ankle thickness and arthritis scores were substantially reduced in IPs treated group than control group, and synovial inflammation, bone erosion and cartilage damage of arthritis were less severe in the IPs-treated groups. Especially, IP2 showed the most significant effect. Conclusion: The apoB derived peptides interacting with ENO1 could have novel therapeutic effect in RA. Reference: [1] Lee, J. Y., et al. (2018). "Apolipoprotein B binds to enolase-1 and aggravates inflammation in rheumatoid arthritis."Ann Rheum Dis77(10): 1480-1489 Disclosure of Interests: None declared